Monozygotic triplets with juvenile-onset autoimmunity and 18p microdeletion involving PTPRM - Herlin, Morten Krogh; Bernth Jensen, Jens Magnus; Andreasen, Lotte; Petersen, Mikkel Steen; Lønskov, Jonas; Thorup, Mette Bendixen; Birkebæk, Niels; Mogensen, Trine H.; Herlin, Troels; Deleuran, Bent (Frontiers in Genetics, 2024)
Abnormal gene dosage from copy number variants has been associated with susceptibility to autoimmune disease. This includes 18p deletion syndrome, a chromosomal disorder with an estimated prevalence of 1 in 50,000 characterized by intellectual disability, facial dysmorphology, and brain abnormalities. The underlying causes for autoimmune manifestations associated with 18p deletions, however, remain unknown. Our objective was to investigate a distinctive case involving monozygotic triplets concordant for developmental delay, white matter abnormalities, and autoimmunity, specifically juvenile-onset Graves' thyroiditis. By chromosomal microarray analysis and whole genome sequencing, we found the triplets to carry a de novo interstitial 5.9 Mb deletion of chromosome 18p11.31p11.21 spanning 19 protein-coding genes. We conducted a literature review to pinpoint genes affected by the deletion that could be associated with immune dysregulation and identified PTPRM as a potential candidate. Through dephosphorylation, PTPRM serves as a negative regulator of STAT3, a key factor in the generation of Th17 cells and the onset of specific autoimmune manifestations. We hypothesized that PTPRM hemizygosity results in increased STAT3 activation. We therefore performed assays investigating PTPRM expression, STAT3 phosphorylation, Th1/Th2/Th17 cell fractions, Treg cells, and overall immunophenotype, and in support of the hypothesis, our investigations showed an increase in cells with phosphorylated STAT3 and higher levels of Th17 cells in the triplets. We propose that PTPRM hemizygosity can serve as a contributing factor to autoimmune susceptibility in 18p deletion syndrome. If confirmed in unrelated 18p/PTPRM deletion patients, this susceptibility could potentially be treated by targeted inhibition of IL-17.